Effect of global atmospheric aerosol emission change on PM2.5-related health impacts. Issue 1 (1st January 2019) - Seposo, Xerxes; Ueda, Kayo; Park, Sang Seo; Sudo, Kengo; Takemura, Toshihiko; Nakajima, Teruyuki
ABSTRACT: Background : Previous research has highlighted the importance of major atmospheric aerosols such as sulfate, through its precursor sulfur dioxide (SO2 ), black carbon (BC), and organic carbon (OC), and their effect on global climate regimes, specifically on their impact on particulate matter measuring ≤ 2.5 μm (PM2.5 ). Policy regulations have attempted to address the change in these major active aerosols and their impact on PM2.5, which would presumably have a cascading effect toward the change of health risks. Objective : This study aimed to determine how the change in the global emissions of anthropogenic aerosols affects health, particularly through the change in attributable mortality (AN) and years of life lost (YLL). This study also aimed to explore the importance of using AM/YLL in conveying air pollution health impact message. Methods : The Model for Interdisciplinary Research on Climate was used to estimate the gridded atmospheric PM2.5 by changing the emission of SO2, BC, and OC. Next, the emissions were utilized to estimate the associated cause-specific risks via an integrated exposure–response function, and its consequent health indicators, AM and YLL, per country. Results : OC change yielded the greatest benefit for all country income groups, particularly among low-middle-income countries. Utilizing either AM or YLL did not alter the order of benefits among upper-middle and high-income countries (UMIC/HIC); however, using either health indicator to express the order of benefit varied among low- and low-middle-income countries (LIC/LMIC). Conclusions : Global and country-specific mitigation efforts focusing on OC-related activities would yield substantial health benefits. Substantial aerosol emission reduction would greatly benefit high-emitting countries (i.e. China and India). Although no difference is found in the order of health outcome benefits in UMIC/HIC, caution is warranted in using either AM or YLL for health impact assessment in LIC/LMIC.